Temporal patterns of roe deer (Capreolus capreolus) traffic accidents in Lithuania: effects of daytime, season and lunar phase - Galinskaitė, Lina; Ignatavičius, Gytautas (International Conference “Environmental Engineering”, 2023)
In many countries road safety and animal protection pose a serious problem due to wildlife-related accidents. Profound information of temporal and spatial patterns of deer-vehicle accidents is necessary for safe mitigation efforts and further accident analysis. We described the temporal patterns of roe deer (Capreolus capreolus) vehicle collisions from 2014 till 2021 in Lithuania. Using a comprehensive dataset, consisting of 19.707 data points, we examined the influence of different time units (i.e., day of year, day of week, month) and moon illumination percentage. Therefore, we identified roe deer peak accident periods within the time units. Highest frequencies of collisions occurred in May, November and December. Between days of the week collisions increased on Friday with a secondary peak on Saturday. Relationships between roe deer vehicle collisions (RDVc) and lunar phases were analyzed, providing evidence for high frequencies of RDVc during full moon illumination. We believe that RDVc are dependent both on human activity in traffic and wildlife activity. Overall, our results highlight, that RDVc disturbance among time is nonrandom. Methods to effective reduce deer-vehicle accidents should be adapted to species-specific temporal periods or place and concentrated to short-term mitigation measures (e.g., speed limits, wildlife warning signs, traffic controls).